Advantages of various approaches by using different nanoparticles in drug delivery - CHANDRA KANT SHARMA; KARISHMA SHARMA; ARCHANA SHARMA; MONIKA SHARMA (International Journal of Pharma and Bio Sciences, 2017)
The emerging applications of nanotechnology in medical field and more precisely in the delivery of drug has been reported in various area of research that includes pharmaceutical sciences which are utilizing nanoparticles in order to minimize the toxic effects as well as side effects of the doses of drugs and their potential improvements by increasing the biocompatibility of nanoparticles in order to intensify the diagnostic as well as therapeutic moieties in to diseased cells with higher efficacy. Specifically at atomic, molecular and supramolecular scale it exhibit fundamentally new properties. Incorporating the prodrugs in to nanotechnology based carrier combines the methods of developing drug invasion and their biocompatibility. Various nanostructure including liposome’s polymers, dendrimers, silicon or carbon material have been detected as well as tested as carriers in drug delivery system. The modern form of approaches are most important when there is inconsistency together with dose and the strength of a remedy in order to understand the extent of transfer of drug from plasma to target region. Cell specific targeting can be achieved by adding the preparations to separately intended transporters.